RESPON CACING PENGGALI TANAH Ponthoscolex Corethrurus TERHADAP BERBAGAI KUALITAS SERESAH - Herwin Setyaningsih; Kurniatun Hairiah; Widyatmani Sih Dewi (Jurnal Tanah dan Sumberdaya Lahan, 2014)
Forest conversion to agriculture systems leads to change on litter input (quantitatively and qualitatively) resulting lower diversity, population density and biomass of earthworm. Litter with ratio C/N <20, or ratio of (lignin (L)+polifenol (P))/N <10 classified as high quality which decomposed rapidly. Six types of litter application were tested i.e. prunning of cofee with the lowest (L+P)/N of 7.5, Gliricidia (L+P)/N of 10, avocado with (L+P)/N of 31, Cofee+Gliricidia with (L+P)/N of 12, Cofee+Gliricidia+ avocado with the highest (L+P)/N of 64. As control soil without litter application was used. Applying tree litters regardless their quality increased significantly (p<0.05) all growth parameters of earthworm, except for Gliricidia application lead to higher level of earthworm mortality starting at 20 days after treatment. Applied a low quality of avocado litter to the soil produced the highest biomass (0.79 g/indiv.), diameter (2.42 mm/indiv.) and length (6.13 cm/indiv.). Mixing coffee litter with Gliricidia litter increased earthworm mortality (5.5% to 42.5%) and reduced production of cocoon (2 become 0 cocoons) compared to coffee applied alone. Coffee+Gliricidia+Avocado lead to longer live earthworm up to 80 days Apparently Gliricidia litter producing chemical substances which harmful to earthworm.Keyword: earthworm, litter quality, forest conversion